Comparison of the Oncological Outcomes Between Robot-Assisted and Abdominal Radical Hysterectomy for Cervical Cancer Based on the New FIGO 2018 Staging System: A Multicentre Retrospective Study - Li, Pengfei; Zhan, Xuemei; Lv, Chifei; Lin, Zhong; Yang, Ying; Wang, Wuliang; Wang, Shaoguang; Hao, Min; Zhu, Bin; Bin, Xiaonong; Lang, Jinghe; Liu, Ping; et al. (Frontiers in Oncology, 2022)
Objective: To compare the 3-year oncological outcomes of robot-assisted radical hysterectomy (RRH) and abdominal radical hysterectomy (ARH) for cervical cancer. Methods: Based on the clinical diagnosis and treatment for cervical cancer in China database, patients with FIGO 2018 stage IA with lymphovascular space invasion (LVSI)-IB2 cervical cancer disease who underwent RRH and ARH from 2004 to 2018 were included. Kaplan-Meier survival analysis were used to compare the 3-year overall survival (OS) and disease-free survival (DFS) rate between patients receiving RRH and those receiving ARH. Cox proportional hazards model and propensity score matching was used to estimate the surgical approach-specific survival. Results: A total of 1137 patients with cervical cancer were enrolled in this study, including the RRH group (n = 468) and ARH group (n = 669). The median follow-up time was 45months (RRH group vs. ARH group: 24 months vs. 60months). Among the overall study population, there was no significant difference in 3-year OS and DFS between the RRH group and the ARH group (OS: 95.8% vs 97.6% p=0.244). The Cox proportional hazards analysis showed that RRH was not an independent risk factor for 3-year OS (HR: 1.394, 95% CI: 0.552-3.523, p=0.482). However, RRH was an independent risk factor for 3-year DFS (HR: 1.985, 95% CI: 1.078-3.655 p=0.028). After 1:1 propensity score matching, there was no significant difference in 3-year OS between the RRH group and the ARH group (96.6% vs 98.0%, p=0.470), however, the 3-year DFS of the RRH group was lower than that of the ARH group (91.0% vs 96.1%, p=0.025). The Cox proportional hazards analysis revealed that RRH was not an independent risk factor for 3-year OS (HR: 1.622, 95%CI: 0.449-5.860 p=0.461), but RRH was an independent risk factor for 3-year DFS (HR: 2.498, 95%CI: 1.123-5.557 p=0.025). Conclusion: Among patients with stage Ⅰ A1 (LVSI +)-Ⅰ B2 cervical cancer based on the FIGO 2018 staging system, RRH has a lower 3-year DFS than ARH, suggesting that RRH may not be suitable for early cervical cancer patients.